Au café jusqu’au bout de la nuit - Florian Bonnefoi (Temporalités)
Emergency measures limiting the opening of places open to the public in the evening were taken during the Covid-19 pandemic and then perpetuated. The crisis became an opportunity for the Egyptian government to legislate on the night. This desire was reiterated in 2022 in the context of the energy crisis. The popular coffee-houses, ahâwî baladî, are among the places targeted by what appears to be an attempt to take back control of the public space. Coffee-houses and night time are associated within a system of often negative representations that involve the figure of the idle man abandoning his home. The will to control time, space and morals are intertwined. However, owners, waiters and customers resist the attempts of public authorities to regulate the night, testifying to the central role of the latter at the economic, social, cultural and recreational levels. In Cairo, the night is indeed a real economic manna and a key moment of daily sociability between men.